The burnout syndrome and job satisfaction in the opinion of nurses - Sowińska, Katarzyna; Kretowicz, Katarzyna; Gaworska-Krzemińska, Aleksandra; Świetlik, Dariusz (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. In an environment filled with emotional tension, nurses are undoubtedly a professional group of high-risk of burnout syndrome. Aim. The aim of the study is to answer the question whether surveyed nurses feel burned out, as well as if they feel satisfied with their job. Material and methods. The material consisted of 96 occupationally active nurses. The study used a method of analysis and critique of literature and the diagnostic survey method, using author’s questionnaire as a research tool. Results and conclusions. Scale of the phenomenon of burnout in the study group is more than half of the respondents. The main reason for the phenomenon of burnout, in the view of respondents, is primarily a low wage, working conditions and misunderstandings among colleagues. Work is a source of satisfaction for the vast majority of respondents. It is necessary to consider education of nurses in the above topic and the inclusion of this occupational group into an increased psychological support.